2002
DOI: 10.1002/app.2359
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan modified by poly(ethylene oxide): Film and mixture properties

Abstract: Chitosan + poly(ethylene oxide) mixtures and films prepared from these mixtures were studied by rheological, absorption of solvent vapors, SANS, and mechanical testing methods. At a stoichiometric chitosan:poly(ethylene oxide) monomer:monomer composition, the mechanical properties of chitosan + poly(ethylene oxide) film are the best as compared with those of the initial components or of other compositions. This film composition is shown to be less heterogeneous. Chitosan and poly(ethylene oxide) are proved to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Different authors have reported on the blending of CHI with cellulose,11 some cellulose ethers,12 starch,13 collagen,14, 15 poly(ethylene oxide),16 water‐soluble tertiary polyamides,17 poly( N ‐vinyl pyrrolidone),18 poly(vinyl alcohol),19 and polymethacrylamidoglucose 20. It was found that CHI has a limited miscibility with cellulose11 and some cellulose ethers12 but is fully compatible with starch 13…”
Section: Introductionmentioning
confidence: 99%
“…Different authors have reported on the blending of CHI with cellulose,11 some cellulose ethers,12 starch,13 collagen,14, 15 poly(ethylene oxide),16 water‐soluble tertiary polyamides,17 poly( N ‐vinyl pyrrolidone),18 poly(vinyl alcohol),19 and polymethacrylamidoglucose 20. It was found that CHI has a limited miscibility with cellulose11 and some cellulose ethers12 but is fully compatible with starch 13…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan/PEO films have been reported to exhibit good mechanical properties because of the specific intermolecular interactions between chitosan and PEO in the blends. Budtova et al [4] have shown that the incompatibility of PEO and chitosan is not strong and does not lead to a phase separation. The AC impedance technique was employed to study the conductivity and dielectric properties of chitosan/PEO blends.…”
Section: Introductionmentioning
confidence: 98%
“…Chitosan is a biopolymer which has oxygen and nitrogen electron donating atoms. Chitosan/PEO films have been reported to exhibit good mechanical properties [9], and blending PEO with chitosan does not lead to a phase separation [10]. Three semiconductor/solid polymer electrolyte junctions of configuration ZnSe/(PEO + chitosan):NH 4 I (+I 2 ) have been assembled and characterized.…”
Section: Introductionmentioning
confidence: 99%